Lenalidomide for Second-line Treatment of Advanced Hepatocellular Cancer: A Brown University Oncology Group Phase II Study. (February 2015) - Safran, Howard; Charpentier, Kevin P.; Kaubisch, Andreas; Mantripragada, Kalyan; Dubel, Gregory; Perez, Kimberly; Faricy-Anderson, Katherine; Miner, Thomas; Eng, Yoko; Victor, Joel; Plette, Angela; Espat, Joseph; et al.
Abstract : Purpose: To assess the activity and toxicity of lenalidomide for patients with advanced hepatocellular cancer (HCC) previously treated with sorafenib. Materials and Methods: Patients with advanced HCC who progressed on or were intolerant to sorafenib were eligible. Patients received lenalidomide 25 mg orally for 1 to 21 days in a 28-day cycle until disease progression or unacceptable toxicities. Results: Forty patients were enrolled and were classified according to the Child-Pugh score: 19 were Child-Pugh A, 16 patients were Child-Pugh B, and 5 were Child-Pugh C. Seventeen patients had extrahepatic disease. Grade 4 neutropenia occurred in 1 of 40 patients (2.5%). Grade 3 fatigue (n=3) and rash (n=4) were the most common nonhematologic toxicities attributable to lenalidomide. Six of 40 patients (15%) had a partial response. Two patients (5%) have not progressed at 36 and 32 months. The median progression-free survival was 3.6 months and the median overall survival was 7.6 months. Conclusions: Lenalidomide can be administered to patients with advanced HCC and hepatic dysfunction. Promising, and in a small percentage of patients, durable activity has been demonstrated. Investigations are needed to explore the mechanism of action of lenalidomide in HCC.